Prognosis of childhood abdominopelvic rhabdomyosarcoma: Case series - Kokoé Agblévi Midékor Gonébo; Moufidath Sounkéré Soro; Rébécca Bonny Obro; Amenan Kan Sophie Kouassi Dria; Sigué Jean Jaurès Ouattara; Yapi Landry Aké; Nicolas Moh Ello (Elsevier, 2023)
Introduction: Rhabdomyosarcoma, the most common malignant mesenchymal tumour in children, primarily affects the urogenitals. In Europe, the prognosis of the localised forms is excellent, whereas in sub-saharan Africa, it is reserved. This observation study aimed to report the diagnostic, therapeutic, evolutionary, and prognostic aspects of rhabdomyosarcoma. Case presentation: This was a series of six observations in four boys and two girls, all of whom had no significant medical history. An abdominal mass in two patients and a pelvic mass in the others evolved over 10 days to 4 months. All localizations were complicated by signs of compression: urinary for the pelvic and digestive for the abdomen. CT tomography revealed urogenital localisation in four patients and abdominal localisation in one patient. A histological examination revealed embryonic rhabdomyosarcoma in all patients. Chemotherapy was neoadjuvant in five patients and postoperative in one patient. Immediate tumour resection was performed in one patient. All patients died: five during chemotherapy and one following recurrence after 1 year of remission. Conclusion: The prognosis of rhabdomyosarcomas is linked to delays in consultation, tumour size, histological type, and therapeutic difficulties. Adequate management of this condition requires multidisciplinary consultation.